Electronic properties of quasi two-dimensional transition metals chalcogenides with low-dimensional magnetism - M. S. Baranava; P. A. Praskurava (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The search for fundamental physical laws which lead to stable high-temperature ferromagnetism is an urgent task. In addition to the already synthesized two-dimensional materials, there remains a wide list of possible structures, the stability of which is predicted theoretically. The article suggests the results of studying the electronic properties of MAX3 (M = Cr, Fe, A = Ge, Si, X = S, Se, Te) transition metals based compounds with nanostructured magnetism. The research was carried out using quantum mechanical simulation in specialized VASP software and calculations within the Heisenberg model. The ground magnetic states of twodimensional MAX3 and the corresponding energy band structures are determined. We found that among the systems under study, CrGeTe3 is a semiconductor nanosized ferromagnet. In addition, one is a semiconductor with a bandgap of 0.35 eV. Other materials are antiferromagnetic. The magnetic moment in MAX3 is localized on the transition metal atoms: in particular, the main one on the d-orbital of the transition metal atom (and only a small part on the p-orbital of the chalcogen). For CrGeTe3, the exchange interaction integral is calculated. The mechanisms of the formation of magnetic order was established. According to the obtained exchange interaction integrals, a strong ferromagnetic order is formed in the semiconductor plane. The distribution of the projection density of electronic states indicates hybridization between the d-orbital of the transition metal atom and the p-orbital of the chalcogen. The study revealed that the exchange interaction by the mechanism of superexchange is more probabilistic.